Pengaruh Konsep Diri terhadap Hubungan Parasosial pada Pembaca Sastra Prosa Fiksi - Syeila Nur Tariza Hadju; Komarudin Komarudin (Yayasan Literasi Sains Indonesia, 2026)
This study aims to determine the influence of self-concept on parasocial relationships in readers of teenlit genre fiction literature. This study uses a quantitative approach method involving 100 female adolescent respondents aged 18–21 years who were limited through purposive sampling techniques. The research instruments are in the form of a self-concept scale and a parasocial relationship scale whose validity and reliability have been tested. Data were analyzed using a simple linear regression test to see the influence between variables. The results of the analysis show that self-concept has a significant effect on parasocial relationships with a significance value of 0.000 (p < 0.05) and an R Square value of 0.121. And the results of the correlation analysis also show that self-concept has a positive and significant relationship with parasocial relationships (r = 0.348; 0.000), which means that both variables run in the same direction, so the higher the reader's self-concept, the higher the possibility of forming a parasocial relationship. These findings indicate that self-concept contributes 12% to parasocial relationships, while the remaining 88% is influenced by other factors outside this study.